Aplikasi sidik serviks untuk meningkatkan pengetahuan dan sikap tentang deteksi dini kanker serviks - Dian Rahmayani; Hesty Widyasih; Tri Maryani (PUINOVAKESMAS, 2021)
Cervical cancer is a malignancy originating from the cervix and is one of the causes of death in women. One of the ways to do early detection of cervical cancer is the VIA test (Visual Inspection with Acetic Acid). Women's awareness is still relatively low to do IVA tests so providing information will enhance knowledge and raise public awareness.  This research is to know the effect of the “SIDIK” Serviks application to the increase of knowledge and attitudes about VIA to reproductive women. Research design applies quasi-experiment with one group pre-test and post-test design. Post-test is done 18 days after pre-test. The research sample of 31 reproductive women. The sampling technique applies purposive sampling. The sample is determined by inclusion and exclusion criteria. The independent variable is Sidik Serviks application and the dependent variable is knowledge and attitudes about VIA. Data collection applies a questionnaire through Google Form to measure knowledge and attitudes. The data analysis uses the Wilcoxon test. The result shows that the average knowledge of pre-test was 17.77, post-test was 19.06 with p-value 0.000, average attitudes of pre-test were 61.03, post-test was 64.16 with p-value 0.000 which means there is an effect of giving Sidik Serviks application on the increase of knowledge and attitudes about VIA.